Special care with special child-oral health status of differently abled children attending special schools in Delhi: A cross-sectional study - Monika Prasad; Basavaraj Patthi; Ashish Singla; Ritu Gupta; Lav Kumar Niraj; Irfan Ali (Wolters Kluwer Medknow Publications, 2018)
Introduction: Oral health is an essential component of overall health. Oral health maintenance is more complex for the physically challenged children; the essential problem is lack of cooperation and coordination because of their physical or mental inability. Thus, physically challenged children are considered as a high-risk group for having dental problems. Aim: The aim of this study is to assess dental caries experience, oral hygiene status, periodontal status, and prevalence of malocclusion among differently abled children attending special schools in Delhi. Materials and Methods: A total of 1060 (610 males and 450 females), differently abled children were included in the study. The children were grouped into visually impaired, hearing and speech impaired, and orthopedic physically challenged only. Clinical examination was recorded using Dentition Status and Treatment Need Index and periodontal status recommended by the World Health Organization (WHO), 2013 and examination for malocclusion was made according to the Dental Aesthetic Index as described by the WHO Oral Health Survey 1997. The Simplified Oral Hygiene Index introduced by John C Greene and Jack R Vermillion in 1964 was used to assess the oral hygiene status. Results: Out of 1060 physically challenged children, 56.4% (598) had dental caries with the mean index or decayed, missing, and filled teeth (DMFT) being 1.10 (standard deviation ±1.26). It was observed that prevalence of dental caries was high in visually impaired group (63.2%) and least in hearing and speech impaired group (51.7%). The overall oral hygiene status recorded was good in 58.5%, fair in 40.8%, and poor in 0.7% of the study population. Conclusion: The cumulative neglect of oral health was seen among the physically challenged children. Children with visual impairment had much more poorer oral health when compared to the hearing and speech impairment and orthopedically physically challenged group. An improved accessibility to dental services as well as dental health education is necessary to ensure that optimum dental care should reach this special group.